Relationship Between Parent Career Behavior with Career Maturity among Syiah Kuala University Students - Ayu Utami Pratiwi; Irin Riamanda; Eka Dian Aprilia; Risana Rachmatan (Da'wa Faculty of Islamic State University Salatiga, 2023)
Career maturity is one of the developmental tasks that students must fulfill as early adults or late adolescents. Good career maturity will affect the selection of a student career life in the future. One of the factors that influence student career maturity is parent career behavior. Parent career behavior is a parent's behavior or parenting style related to a child's career. This research uses quantitative research methods with a correlation approach. The purpose of this study was to see a relationship between parent career behavior and career maturity in Syiah Kuala University students. Sampling using a nonprobability sampling technique of quota sampling type with a total of 332 research respondents. The results showed that there was a positive relationship between parent career behavior and career maturity in Syiah Kuala University students. The hypothesis test was carried out using the Spearman Correlation technique and obtained a significance value (p)=0.000 (p<0.05) and a correlation coefficient value (r)=0.428. In addition, the results of the study also showed that most respondents were in the category of career maturity and moderate parent career behavior.